Penguatan Identitas Budaya Lokal dalam Menghadapi Masuknya Budaya Luar di Era Globalisasi - Gunawan Risky (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
The influx of foreign cultures in the era of globalization has significantly weakened local cultural identity, particularly among communities and younger generations who are increasingly exposed to global popular culture. This condition is an important reason to conduct community service activities focused on strengthening local cultural identity, as an effort to preserve the community's self-identity and socio-cultural resilience. This service activity aims to increase the public's understanding, awareness, and positive attitude toward local cultural values amid external cultural influences. The service method used is a participatory-educational approach through cultural socialization, guided group discussions, and local culture-based practical activities. The evaluation was conducted using pre- and post-test questionnaires, observations, and brief interviews to measure changes in community attitudes and sociocultural aspects. The results of the activities show an increase in community understanding and awareness of the importance of local cultural identity, increased participation in cultural activities, and the emergence of potential for utilizing local culture as a source of social and creative economic development. This activity underscores that community service rooted in local culture plays a strategic role in strengthening community identity and serves as an important foundation for sustainable cultural preservation amid the forces of globalization.